Biological Alteration of Flow Properties of Soil Samples From Two Bt Horizons of a Haplic Luvisol Determined With Rheometry - Haas, Christoph; Holthusen, Dörthe; Horn, Rainer (Frontiers in Environmental Science, 2018)
Flow properties of soils are helpful to describe the soils' response on mechanical loading, which occurs naturally (e.g., caused by growing roots or drilling earthworms) or anthropenically (e.g., in the course of management practices like tillage) In order to determine the effect of bacterial or plant exudation induced changes of soil strength and soil's flow behavior soil samples of the Bt horizons of a haplic Luvisol were saturated with pure water or with aqueous solutions of biological model substance. We chose xanthan gum as a bacterial exudate which represents the chemical alteration of soil microorganism, while polygalacturonic acid has been used as a root's mucilage analog. Surface tension and viscosity of these aqueous solutions were determined, and soil samples' flow properties were obtained with the help of rheometry. By applying amplitude sweep tests to the soil samples soil stability related parameters were determined [loss (G″) and storage (G′) moduli, representing the plasticity or elasticity of soils, respectively] or calculated [namely, the loss factor (ratio of G‴ and G′), Integral Z (a strain-stress dependent sum-parameter) and the linear viscoelastic range (where no changes in soil structure occur)]. We hypothesized that (I) flow properties of used model substances differ from those of pure water and, (II) biological model substances influence the water content at defined matric potential caused by e.g., altered surface tension, thus influencing parameters that were related to soil stability. Furthermore, (III) the impact of biological model substance depends on the shear rate that is applied to achieve the soil's deformation because some biological model substances show non-Newtonian flow. So far and to our knowledge this is the first rheological work on soils that evaluates the effect of differing shear rates on elastic and plastic deformation statistically. We found the impacts of biological model substances on soils' flow properties to be not only dependent of origin (plan or bacterial), concentration and matric potential, but also on deformation intensities. Due to chemical particularities of PGA a deformation induced soil stabilization was observed. Leading to the conclusion that deformation processes e.g., in the rhizosphere are much more complex than previously thought.